Adoption issues - Healey, Justin (Issues in society (Balmain, N.S.W.), 2011)
There has been an overall decline in the number of adoptions of Australian children over the last 25 years, however past and present adoption practices continue to raise a number of challenging and complex emotional and practical issues. This book examines the adoption experience in Australia, including local and intercountry adoption and the legal processes involved; adoption trends; identity and disclosure issues; the impacts of past coercive adoption practices on unmarried birth mothers and their children; post-adoption grief and loss; and the same-sex adoption law debate. A number of perso.